Pengaruh Pengembangan Karier danÂ Penilaian Kinerja terhadap Kepuasan Kerja Melalui Komitmen Kerja Karyawan Koperasi Agrobisnis Tarutama Nusantara Jember - M. Syaharudin; Haikal Auzan Syah; Budi Nurhardjo (UPT Penerbitan Universitas Jember, 2018)
The articles in this research aims to know the influence of career development and performance assessment against job satisfaction through a work commitment. The study categorized as research description (explanatory research).This research is done in cooperative Agribusiness Tarutama Nusantara Jember. The population in this research is the employees remain in the Cooperative Agribusiness Tarutama Nusantara Jember as much as 159 employees. Large samples in this study using multivariate statistics 115 IE rules sample. Data were collected using a questionnaire. Data analysis in this study includes test instruments, test the classical assumptions, test , and an analysis of the Path. The results of the research there is a partial influence and simultaneous development of performance assessment and career I to wards job satisfaction through employee commitment. This suggests that the performance appraisal,job satisfaction and commitment of work has a positive influence to wards the development of a career. Keywords: Employee Performance, Work Environment, Motivation Work, Work Experience